Implementasi Model Pembelajaran Tipe Sfae terhadap Hasil Belajar Siswa Kelas IV Sekolah Dasar - Andika Aryanti; Noviardani Kartika Prameswari (Medan Resource Center, 2022)
This research aims to describe and notify the students’ response towards the learning method of cooperative learning model (student facilitator and explaining) as well as describing and knowing the learning outcomes for students at fourth grade following the implementation of the cooperative learning model (student facilitator and explaining). This research follows the qualitative method by following the survey and test techniques to collect the data. There were 27 students in a class that were considered as the data. The researcher then analyzes the data descriptively and qualitatively.The research found that the students’ response was positive meaning that the cooperative learning model (student facilitator and explaining) worked and helped students’ marks to meet the satisfaction. With that being said, the researcher met the conclusion that the cooperative learning model has significantly improved the students’ result of fourth graders at SD Muhammadiyah 1 Menganti.